Plant growth conditions alter phytolith carbon - Gallagher, Kimberley L.; Alfonso-Garcia, Alba; Sanchez, Jessica; Potma, Eric O.; Santos, Guaciara M. (Frontiers in Plant Science, 2015)
Many plants, including grasses and some important human food sources, accumulate and precipitate silica in their cells to form opaline phytoliths. These phytoliths contain small amounts of organic matter (OM) that are trapped during the process of silicification. Previous work has suggested that plant silica is associated with compounds such as proteins, lipids, lignin and carbohydrate complexes. It is not known whether these compounds are cellular components passively encapsulated as the cell silicifies, polymers actively involved in the precipitation process or random compounds assimilated by the plant and discarded into a "glass wastebasket". Here, we used Raman spectroscopy to map the distribution of OM in phytoliths, and to analyze individual phytoliths isolated from Sorghum bicolor plants grown under different laboratory treatments. Using mapping, we showed that OM in phytoliths is distributed throughout the silica and is not related to dark spots visible in light microscopy, previously assumed to be the repository for phytolith OM. The Raman spectra exhibited common bands indicative of C-H stretching modes of general OM, and further more diagnostic bands consistent with carbohydrates, lignins and other OM. These Raman spectra exhibited variability of spectral signatures and of relative intensities between sample treatments indicating that differing growth conditions altered the phytolith carbon. This may have strong implications for understanding the mechanism of phytolith formation, and for use of phytolith carbon isotope values in dating or paleoclimate reconstruction.